Supporting the Bridge: Partnering Catechism and Havruta Text Study for the Religious Education of Children - Cash, Emily M. H. (Pro ecclesia, 2024)
This article argues that the Jewish practice of havruta text study has the potential to nuance and enrich the spiritual formation of Christian children by addressing the theological and pedagogical liabilities of catechisms. By scaling and employing the practice of havruta for children, Christian catechists could create opportunities for children to wield the ideological materials apprehended through catechisms, making textual study a formative educational encounter. Havruta text study, rather than merely transmitting doctrines, has the potential to confer spiritual dignity, to encourage interpretive exploration, and to forge a capacity for constructive theological dialogue. These potential contributions of havruta, aside from enriching the spiritual formation of individual children, would build theological resilience, lay groundwork for Christian unity, and open the church to vital new interpretative possibilities.